Effects of moringa oleifera on glycaemia and insulin levels: A review of animal and human studies (2019)
Diabetes and related neurological complications are serious worldwide public health problems. The increasing number of affected individuals make it necessary to implement novel nutritional and therapeutic interventions. The tree Moringa oleifera (MO) has been used as a food source and for traditional medicine purposes due to possible antihyperglycemic, antioxidant, anti-inflammatory, and lipid regulating properties. These properties may be explained by the presence of numerous phytochemicals in the leaves, fruits, roots and, oil of the tree. The evidence for acute antihyperglycemic effects of MO extract on diabetic animal models seems to be robust, but more chronic and long-term studies are needed. In contrast, the hypoglycemic effects of MO on humans are not as clear. The scarce number of human studies, together with a diverse range of methodologies and MO doses, may explain this. In addition, evidence regarding changes in insulin levels due to MO intervention is ambiguous, both in animal and human studies. Therefore, more structured studies are needed to clarify if MO has an effect on insulin levels or activity. © 2019 by the authors. Licensee MDPI, Basel, Switzerland.